Seroprevalence of SARS-CoV-2 Infection among Vaccinated Health Workers and Hospital Staff - Colmenares-Mejía, Claudia C; Quintero-Lesmes, Doris C; Acosta, Isail Salazar; Suárez, Diana Paola; Meneses, Ligia; Rincón, Olga Lucia Sopó; Bautista-Niño, Paula K; Norma (Archives of Clinical and Biomedical Research, 2022)
Frontline healthcare workers are critical for a timely response to SARS-CoV-2 pandemic. An observa-tional cross-sectional study, with three evaluations, was conducted. For each evaluation, RT-PCR and IgM/IgG antibodies tests were performed. 1,118 participated in round-1; 862 in round-2 and 753 in round-3 were included. Presence of infection was lower in round-1 (1.3% vs 2.8% vs 2.3%). Adjusted seropositivity decreased for round-3 [37.5% (95%CI 34.3-40.3), 36.7% (95%CI 33.5-39.8), 23.2% (95%CI 20.3-26.2)]. Participants with a previous PCR+ had a higher frequency of seropositivity [65.7% (95%CI 60.6-70.6)]. We identified asymptomatic health personnel positive for SARS-CoV-2 and low seroprevalence compared with other reports.